2019
DOI: 10.1136/archdischild-2019-317280
|View full text |Cite
|
Sign up to set email alerts
|

Deferred consent for delivery room studies: the providers’ perspective

Abstract: ObjectiveTo gain insight into neonatal care providers’ perceptions of deferred consent for delivery room (DR) studies in actual scenarios.MethodsWe conducted semistructured interviews with 46 neonatal intensive care unit (NICU) staff members of the Leiden University Medical Center (the Netherlands) and the Hospital of the University of Pennsylvania (USA). At the time interviews were conducted, both NICUs conducted the same DR studies, but differed in their consent approaches. Interviews were audio-recorded, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…First, data were unavailable for why deferred consent was chosen. Second, we did not ascertain patients' and providers’ perspectives on deferred consent, though prior literature has shown that both groups find it to be an acceptable alternative [ 13 , 14 ]. Third, this was an exploratory and post-hoc analysis, and thus we did not test for statistical significance and our findings require replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, data were unavailable for why deferred consent was chosen. Second, we did not ascertain patients' and providers’ perspectives on deferred consent, though prior literature has shown that both groups find it to be an acceptable alternative [ 13 , 14 ]. Third, this was an exploratory and post-hoc analysis, and thus we did not test for statistical significance and our findings require replication.…”
Section: Discussionmentioning
confidence: 99%
“…Deferred consent has several possible benefits including decreasing the time to study enrollment, allowing for enrollment when study personnel are unavailable [ 9 , 10 ], and allowing the inclusion of populations less represented in clinical trials [ 4 , 11 , 12 ]. Multiple studies have identified that deferred consent is considered an acceptable substitute for pre-enrollment consent by both participants and clinicians [ 13 , 14 ]. Our objective was to assess patient-level characteristics, adherence, and rate of withdrawal among participants enrolled with consent obtained before (nondeferred consent) vs. after (deferred consent) randomization in the COVID-PRONE randomized trial (NCT04383613).…”
Section: Introductionmentioning
confidence: 99%
“…This approach implies that parents are approached by a midwife/obstetrician for a blanket opt-out consent for DR studies that went through rigorous scientific and ethics review. Like neonatal care providers that were interviewed in our earlier study [11], interviewed parents suggested the prenatal opt-out as a possible addition to improve the deferred consent approach, but doing so would not absolve investigators of informing parents of eventual study participation of their infant, nor of obtaining consent for the usage of already obtained data. In contrast, various parents reported that consent could fully be waived in the case of observational DR studies.…”
Section: Discussionmentioning
confidence: 99%
“…As part of a research project studying ethical aspects of recording and reviewing neonatal resuscitation [9][10][11][12], we conducted interviews with parents of very and extremely premature infants. One of the objectives for the study was to provide insight into parental perceptions of consent for using recordings of neonatal resuscitation for various purposes, including DR studies.…”
Section: Introductionmentioning
confidence: 99%
“…In neonatal research, this may be considered in trials on delivery room management,5 where DC has been used before,6 but is deemed ethically and legally complex 7. The alternative, prenatal consent, was reported to negatively impact on validity and representativeness 8 9.…”
Section: Objectivementioning
confidence: 99%